Production of hydrogen over Ni/carbonaceous catalyst. (15th October 2020) - Lestinsky, P.; Zikmund, Z.; Grycova, B.; Ryczkowski, R.; Grams, J.; Inayat, A.
Highlights: H2 is produced by dry reforming of CH4 and catalytic cracking of organic vapours. Carbonaceous catalysts are prepared from waste biomass using microwave pyrolysis. Carbonaceous catalyst with 13.2 wt.% of Nickel gives highest conversion. Macroporous morphology of carbonaceous catalyst resembles honeycomb structure. Abstract: Catalytic materials for hydrogen production were synthesized by impregnating waste spruce sawdust with nickel nitrate followed by microwave pyrolysis. Ni/carbonaceous materials thus obtained were tested as catalyst for dry reforming of methane as well as for upgrading of organic vapours from biomass pyrolysis. Among five samples synthesized with different amount of Ni on carbonaceous support, the sample with 13.2 wt% Ni showed the highest CH4 and CO2 conversion for dry reforming at 800 °C. The yields of 31.4 vol% for H2 and 39.0 vol% for CO were recorded. The catalyst sample exhibited only a small decrease in activity after 6 h of time-on-stream. The same sample was applied as catalyst for upgrading of organic vapours from thermal pyrolysis of spruce sawdust and cellulose. A considerable increase in H2 content (i.e. from 1.2 to 14.1 mmol g −1 ) in the product mixture was observed. The main advantage of using carbonaceous support is its resistance towards rapid deactivation due to coke deposition. This advantage can be exploited by using it as catalyst support in reactions that suffer from such catalyst deactivation. Furthermore, the honeycomb-like structure and morphology of carbonaceous materials can promote mass transfer around catalytically active sites that can be beneficial in reactions involving large molecules.